2013
DOI: 10.1061/(asce)em.1943-7889.0000588
|View full text |Cite
|
Sign up to set email alerts
|

Time-Variant Strength Capacity Model for GFRP Bars Embedded in Concrete

Abstract: Glass fiber-reinforced polymer (GFRP) concrete reinforcement exhibits high strength, is lightweight, can decrease time of construction, and is corrosion resistant. However, research has shown that chemical reactions deteriorate the GFRP reinforcing bars over time, resulting in a reduced tensile capacity. This paper develops a time-variant probabilistic model to predict the tensile capacity of GFRP bars embedded in concrete. The developed model is probabilistic to properly account for the relevant sources of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Trejo et al [24] reported experimental tension test data for over one hundred GFRP reinforcement embedded in concrete and exposed to actual environmental conditions (mean annual temperature of 23 °C and average annual precipitation of 1008 mm) for seven years. Based on this study, Gardoni et al [25] developed the time-variant model. Later, time-dependent reliability analysis on a bridge deck was analyzed [26].…”
Section: Introductionmentioning
confidence: 99%
“…Trejo et al [24] reported experimental tension test data for over one hundred GFRP reinforcement embedded in concrete and exposed to actual environmental conditions (mean annual temperature of 23 °C and average annual precipitation of 1008 mm) for seven years. Based on this study, Gardoni et al [25] developed the time-variant model. Later, time-dependent reliability analysis on a bridge deck was analyzed [26].…”
Section: Introductionmentioning
confidence: 99%
“…In severe alkaline concrete environment, the mechanical performance degradation of the GFRP reinforcing bars is closely related to the alkaline solution diffusion coefficient [21][22][23][24][25][26]. Katsuki and Uomoto [21] suggest the relationship between the tensile strength variation and the alkaline diffusion coefficient of FRP reinforcing bars.…”
Section: Diffusion Coefficient Of Alkaline Solutionmentioning
confidence: 99%
“…, the new models are formulated in a probabilistic manner (see Equations 7-9 and 7-10 for and , respectively) to account for the high degree of uncertainty while incorporating CNTs, statistical uncertainty in estimation of the unknown model parameters, model error associated with inexact form of the model, and missing of the possible influential variables that might influence the mechanical properties[222,234].= ɳ ( , ) × ɳ ( , ) × ɳ ( , ) × [1, ), ɳ ( , ), and ɳ ( , ) are dispersion relation, hydration age relation, and matrix relation, respectively, − is the volume fraction of CNTs within the cement matrix, and . Note that because − used in cementitious materials is very low (0.000038-0.001277; based on the database), the predicted elastic modulus of CNT-cement nanocomposites is almost the same as the matrix elastic modulus.…”
mentioning
confidence: 99%